2012
DOI: 10.1038/bjc.2012.177
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 and its receptor CXCR2 in the tumour microenvironment promote colon cancer growth, progression and metastasis

Abstract: Background:Colorectal cancer (CRC) is a leading cause of death in the United States. Increased level of interleukin-8 (IL-8) and CXCR2 on tumours and in the tumour microenvironment has been associated with CRC growth, progression and recurrence in patients. Here, we aimed to evaluate the effects of tissue microenvironment-encoded IL-8 and CXCR2 on colon cancer progression and metastasis.Methods:A novel immunodeficient, skin-specific IL-8-expressing transgenic model was generated to evaluate colon cancer growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
213
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(223 citation statements)
references
References 43 publications
0
213
2
Order By: Relevance
“…IL8 is a known potent proinflammatory cytokine that exerts its effects through binding to its G protein-coupled receptors CXCR1 and CXCR2. Extensive work in solid tumors has shown that IL8 is critical in survival, invasion, and proliferation of cancer cells [21][22][23][24] and might be an important regulator of cancer stem cell activity. [25][26][27] Activation of multiple pathways by IL8, including phosphatidylinositol 3-kinase/protein kinase B (AKT), phospholipase C/protein kinase C, and mitogen-activated protein kinase (MAPK) signaling, leads to increased expression of various The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…IL8 is a known potent proinflammatory cytokine that exerts its effects through binding to its G protein-coupled receptors CXCR1 and CXCR2. Extensive work in solid tumors has shown that IL8 is critical in survival, invasion, and proliferation of cancer cells [21][22][23][24] and might be an important regulator of cancer stem cell activity. [25][26][27] Activation of multiple pathways by IL8, including phosphatidylinositol 3-kinase/protein kinase B (AKT), phospholipase C/protein kinase C, and mitogen-activated protein kinase (MAPK) signaling, leads to increased expression of various The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the growth of residual tumor deposits may be stimulated since IL-8 has been shown to promote tumor growth in numerous experimental studies (19,20,23). It is also possible that IL-8, via different mechanisms, may encourage tumor angiogenesis (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 has also been shown to promote angiogenesis, tumor growth, and metastasis in several murine models (18). IL-8 is notably upregulated in colorectal and other cancer types and has been shown to promote angiogenesis as well as enhance proliferation and survival of tumor cells through autocrine activation (18)(19)(20). In addition exogenous IL-8 has been shown to stimulate tumor cell proliferation (21).…”
Section: Introductionmentioning
confidence: 99%
“…CXCL8 was reported to activate MMP expression (33) and suppress tissue inhibitor of metalloproteinases expression (60), and these regulations by CXCL8 are responsible for the rupture of atherosclerotic plaques. In human macrophages and macrophage-derived foam cells, CCL15 is capable of inducing the production of MMP-9 (27), whose expression is regulated by STAT3 (28), whereas CXCL8 is apparently involved in the recruitment of human NK cells to sites of early viral infection by mast cells (61) and metastasis of colon cancer (62). The release of CXCL8 activates CXCR2, which is coexpressed with CCR1 in macrophages (39) and human mast cells (63,64), leading to STAT3 Tyr 705 phosphorylation (65).…”
Section: Discussionmentioning
confidence: 99%